2020
DOI: 10.1007/s10933-020-00115-3
|View full text |Cite
|
Sign up to set email alerts
|

A guide to the identification of subfossil non-chydorid Cladocera (Crustacea: Branchiopoda) from lake sediments of Central America and the Yucatan Peninsula, Mexico: part I

Abstract: Cladocera (Crustacea: Branchiopoda) quickly respond to changes in environmental conditions and their remains are usually found in large amounts in lacustrine sediments, which make them an important biological proxy in paleolimnological studies. Variations in species composition have been used to infer paleo-climate and paleo-environmental variables including lake depth, eutrophication, and deforestation. However, despite their advantages as bioindicators in the study of past conditions, they are underutilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Although scarce, Sminov and Elías-Gutiérrez [41] found eight cladoceran genera after a survey in sediments from 25 systems in Yucatan. For example, recent studies on 56 systems from Mexico and Central America [45,46] found only three taxa in five out of 19 systems located in the Yucatan Peninsula. These numbers indicate, as Smirnov & Elías-Gutiérrez [41] suggested, that cladocerans preference for littoral areas and their rapid decomposition in the bottom mud impedes preservation.…”
Section: Metabarcoding and Ednamentioning
confidence: 99%
“…Although scarce, Sminov and Elías-Gutiérrez [41] found eight cladoceran genera after a survey in sediments from 25 systems in Yucatan. For example, recent studies on 56 systems from Mexico and Central America [45,46] found only three taxa in five out of 19 systems located in the Yucatan Peninsula. These numbers indicate, as Smirnov & Elías-Gutiérrez [41] suggested, that cladocerans preference for littoral areas and their rapid decomposition in the bottom mud impedes preservation.…”
Section: Metabarcoding and Ednamentioning
confidence: 99%
“…was especially abundant in the intraclast sample as well. Specimens of this taxon are generally found in the pelagic zone of deeper lakes, however, Wojewódka et al (2016Wojewódka et al ( , 2020a reports this genus also in much shallower waterbodies (max. depth of approximately 2 m).…”
Section: Sedimentary Facies and Past Lake Water Levelsmentioning
confidence: 98%
“…Three to four slides (0.1 cm 3 each) were analysed for each sample at 100×, 200× and 400× magnification. Identification was made following Wojewódka et al (2020aWojewódka et al ( , 2020b. The most common cladoceran remains, such as head shield, shell, postabdomen were identified, and at least 70 individuals were counted for each sample (Kurek et al, 2010).…”
Section: Biological Proxiesmentioning
confidence: 99%